Il principio d’eguaglianza nell’ambito del Biodiritto (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The article deals with the principle of equality in the field of biolaw. It takes into consideration some examples concerning fundamental rights and freedom, in the light of the relationship between law and science. It considers informed consent as an instrument of equality and analyses the role played by science in the field of biolaw.
Keywords: Equality; informed consent; law and science; end of life decisions; human dignity